Critical Dementia Studies An Introduction - Ward, Richard; Sandberg, Linn (Dementia in Critical Dialogue, 2023)
This book puts the critical into dementia studies. It makes a timely and novel contribution to the field, offering a thought-provoking critique of current thinking and debate on dementia. Collectively the contributions gathered together in this text make a powerful case for a more politically engaged and critical treatment of dementia and the systems and structures that currently govern and frame it. The book is inter-disciplinary and draws together leading dementia scholars alongside dementia activists from around the world. It frames dementia as first and foremost a political category. The book advances both theoretical and methodological thinking in the field as well as sharing learning from empirical research. Outlining the limits to existing efforts to frame and theorise the condition, it proposes a new critical movement for the field of dementia studies and practice. The book will be of direct interest to researchers and scholars in the field of dementia studies and wider fields of health, disability and care. It will provide a novel resource for students and practitioners in the fields of dementia, health care and social care. The book also has implications for dementia policymaking, commissioning and community development. The Open Access version of this book, available at http://www.taylorfrancis.com, has been made available under a Creative Commons Attribution-Non Commercial-No Derivatives 4.0 license.